Development of a Cuvette-Based LSPR Sensor Chip Using a Plasmonically Active Transparent Strip - Oh, Seo Yeong; Heo, Nam Su; Bajpai, Vivek K.; Jang, Sung-Chan; Ok, Gyeongsik; Cho, Youngjin; Huh, Yun Suk (Frontiers in Bioengineering and Biotechnology, 2019)
This research demonstrates the development of a transmission-mode localized surface plasmon resonance (LSPR) sensor chip using a cuvette cell system for the sensitive detection of a biomolecule marker such as C-reactive protein (CRP). In order to develop a highly sensitive LSPR sensor chip, plasmonically active gold nanoparticles (AuNPs) were decorated onto various transparent substrates in the form of a uniform, high-density single layer using a self-assembly process. The transparent substrate surface was modified with amine functional groups via (3-Aminopropyl)triethoxysilane (APTES) treatment, and the ligand concentration and temperature (0.5% APTES at 60 °C) were then optimized to control the binding energy with AuNPs. The optimized plasmonically active strip was subsequently prepared by dipping the amine-functionalized substrate into AuNPs for 8 h. The optimized plasmonic strip functionalized with anti-CRP was transformed into a portable LSPR sensor chip by placing it inside a cuvette cell system, and its detection performance was evaluated using CRP as a model sample. The detection limit for CRP using our LSPR sensor chip was 0.01 μg/mL, and the detection dynamic range was 0.01 to 10 μg/mL with a %CV of less than 10%, thus confirming its selectivity and good reproducibility. These findings illustrate that the highly sensitive portable LSPR biosensor developed in this study is expected to be widely used in a diverse range of fields such as diagnosis, medical care, environmental monitoring, and food quality control.